Quantitative measurements of force distribution in single and multi cellular systems - Ulmer, Jens (2005)
Tissue formation and organ development in animals is a complex, lifelong process. The building blocks of tissue are living cells surrounded by secretion products, mostly proteins and polysaccharides. Aggregates of these proteins have different structural geometries and functionalities depending on localization and task in vivo. They form the extracellular matrix (ECM). The detailed quantitative evaluation of tissue construction and tissue-cell interaction is essential for a detailed understanding of organ development and its associated malfunctions which lead to different diseases. However, quantitative studies of cellular events in vivo are restricted since high resolution techniques characterizing cell functions are not suitable for living organism. In respect to tissue culture techniques, introduction of artefacts in mammalian cells cultured on flat, rigid and non-natural two dimensional surfaces is apparent. Such surfaces do not possess three dimensionality and variation of compliance on the micrometer scale as observed in the ECM. To circumvent this drawback new materials and techniques are needed, where surface compliance, structural geometry and chemical composition of ECM models can be adjusted independently. In addition, local force and compliance measurements should produce new insights in cell-ECM interaction and tissue development. The first two parts of this thesis describe a novel micro-engineered mechanical device which serves as a platform for constructing ECM models and as force sensor array. We developed a transparent elastic surface with arrays of micrometer scaled posts. The development process is based on standard photolithographic techniques. Typical structural dimensions of posts are a diameter of 2.5 micro m a height of 15 micro m. Physical properties of post arrays such as local and macroscopic substrate elasticity were investigated quantitatively. These posts were shown to be able to serve as a quantitative device measuring local forces down to the nanonewton range implied by the calibration analysis. The micro-array offers a template for constructing the ECM in vitro with different chemical and mechanical constitutions of the ECM as well as different geometries. The tops of posts were selectively functionalized with either a peptide sequences (arginine-glycine-aspartate, cRGD) or an amorphous matrix protein resulting in well defined surfaces suitable for quantitative force measurements of living cells. By exploring the impact of surface tension of air-water interfaces from protein solution in close contact with a micro-array, the force dependence of fibronectin fibre formation was shown. Part III describes the application of force sensor arrays for measuring an adherent cells spatial distribution of local forces along its membrane. Therefore rat embryonic fibroblasts with GFP fusion proteins to paxilin and beta3 integrin were used to localize the focal adhesions with fluorescence microscopy under physiological conditions. Correlation of patch size to generated force revealed local stress values from 0.1 ± 1.5 up to 115 ± 15.1 nN/micro m2 as a function of cell-state. Using surfaces with different pliabilities by variation of post height and chemical functionality, it was possible to investigate different morphological states of adhesion sites in human foreskin fibroblasts (HFF). The molecular composition of focal contacts strongly depends not only on local substrate stiffness but also on the global compliance of the surface. In the case of fibronectin coated microarrays development of focal contacts was strongly dependent on stiffness of the underlying support. However, post arrays with different compliance and coated with cRGD demonstrated that local mechanosensing capabilities of focal contacts is also assisted by different mechanisms which sense global mechanical properties of cells environment. The mechanical interplay in a multicellular system was investigated in the last part of this work. During organ development cells aggregate and form multicellular compartments in a very precise manner. In order to maintain regular organ function it is important that cell can communicate during organogenesis. The communication pathways based on biochemical signalling have been extensively investigated over the past twenty years. Madin-Darby Canine Kidney (MDCK) cells form functional cellular aggregates, termed cysts under special conditions in vitro. The conditions were adapted to induce cyst growth on force sensor arrays allowing precise force mapping during cyst development. These data were analysed to verify a computational model calculating of surface-forces generated by MDCK cysts inside a 3 dimensional cell culture system. Switching to a mechanical anisotropic environment meant that MDCK cysts no longer grew as round spheres. Instead cell aggregates generated tubular shapes. So far, tubulogenesis in vitro was only inducible by adding growth factors to the culture medium.
Keywords: Hochschulschrift